Testing the Mediating Role of Emotional Exhaustion on the Relationship between Workload and Work Stress on Employee Performance - Rini Juni Astuti; Muhammad Yazid Zidan (ITB AAS Indonesia Surakarta, 2025)
This study aims to investigate the impact of workload and work stress on employee performance, with emotional exhaustion serving as a mediating variable. The research was conducted on employees of the Bintang Indokarya Gemilang company, with a sample size of 180 respondents. The collected data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings suggest that high levels of workload and work stress in the workplace have a negative impact on employee performance and increase emotional exhaustion. Additionally, the results show that emotional exhaustion partially mediates the relationship between workload and work stress on employee performance. This research is expected to contribute to both the company and other entities by emphasizing the importance of managing employee workloads to enhance performance, ultimately aiding in the achievement of organizational objectives